2017
DOI: 10.1111/rda.13050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of housing system on reproductive behaviour and on some endocrinological and seminal parameters of donkey stallions

Abstract: Reproductive management of male donkeys employed for artificial breeding has been poorly studied. The aim of this study was to evaluate the effect of housing system, with the animals grouped together in a paddock or kept in individual boxes, on sexual behaviour, cortisol and testosterone concentration and seminal characteristics of adult male donkeys. The study included four Amiata donkey jacks (stallions) from which ejaculates, saliva and blood were collected during two distinct 3 weeks periods, one in the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…They are important for the tourist industry and recently have become popular as pets (Thiemann and Rickards, 2013;El-Shafaey et al, 2017;Salem et al, 2018). The scientific literature has shown increased interest in their welfare (Rota et al, 2018), in donkeys' infectious diseases (Laus et al, 2015;Barrandeguy and Carossino, 2018;Sgorbini et al, 2018), alternative therapies (Bonelli et al, 2016a), and in specific diagnostic criteria and reference values in adults (Meucci et al, 2015;Sgorbini et al, 2017;Bonelli et al, 2019), pregnant and lactating jennies (Crisci et al, 2014;Bonelli et al, 2016b;Carluccio et al, 2016), and donkey foals (Sgorbini et al, 2013;Veronesi et al, 2014;Carluccio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They are important for the tourist industry and recently have become popular as pets (Thiemann and Rickards, 2013;El-Shafaey et al, 2017;Salem et al, 2018). The scientific literature has shown increased interest in their welfare (Rota et al, 2018), in donkeys' infectious diseases (Laus et al, 2015;Barrandeguy and Carossino, 2018;Sgorbini et al, 2018), alternative therapies (Bonelli et al, 2016a), and in specific diagnostic criteria and reference values in adults (Meucci et al, 2015;Sgorbini et al, 2017;Bonelli et al, 2019), pregnant and lactating jennies (Crisci et al, 2014;Bonelli et al, 2016b;Carluccio et al, 2016), and donkey foals (Sgorbini et al, 2013;Veronesi et al, 2014;Carluccio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Erection was obtained in all but three collections (one after saline and two after cloprostenol sodium administration) after female contact, showing the necessity of sexual stimulation to awake sexual activity, and, probably, an exclusive action of cloprostenol sodium on the penis erectility, as demonstrated in vitro in several species [18,30]. The interval from courtship to mount and ejaculation in the donkey species is longer than in horses [12,13,15,30]. The inter-male variation regarding the minimal time necessary for semen collection or mating has been well documented.…”
Section: Discussionmentioning
confidence: 72%
“…Collecting semen from donkey jacks is often a time consuming and frustrating practice. The time needed to obtain an erection followed by ejaculation varies from 6 to 32 min when mounting estrus jennies [11][12][13] or estrus mares [14]. In a study of natural mating, the time between the introduction of the jack in the 'jennies' pen and the first mount with ejaculation varied between 25 and 93 min [15].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Rota et al (2008) comparing three extenders in donkey sperm found a mild decline in total motility after 72 h incubation. Later studies, however, showed a rapid decline in donkey sperm kinetics already after 24 h storage at þ4°C (Rota et al, 2018). Contri et al (2010) reported an extender-and season-dependent sperm activity decline during storage (in autumn faster than in spring).…”
Section: Discussionmentioning
confidence: 97%